061 Training in headache in australia, new zealand and asia. (29th July 2019) - Zhang, Lin; Jenkins, Bronwyn; Stark, Richard; Hutton, Elspeth
Abstract : Introduction: Migraine is the leading cause of age-adjusted neurological disability in Australia, but little is known about headache training in our region. We aimed to assess the quantity of teaching in headache subjects during undergraduate and postgraduate years. Method: This is a cross-sectional survey study where questionnaires were sent to 137 delegates from Australia, New Zealand and Asia, prior to the Headache Master School in Sydney in August 2018. The Main outcome measured are recalled number of hours of teaching in undergraduate year and postgraduate years in: 1) Migraine; 2) Trigeminal autonomic cephalalgias (TACs); 3) Asthma; 4) Myasthenia gravis (MG). Results: The questionnaire response rate was 73% (100 of 137), of which 29 delegates were within 10 years of completing their undergraduate degree and 98 were neurologists. In undergraduate training, there was much greater quantity of teaching in asthma than migraine (Z=5.007, p<0.000) despite both being high-prevalent (asthma 11%, migraine 15–20%) conditions. Similarly, for diseases of medium-to-low prevalence, there was less training in TACs (1/1000), compared to MG (1.2/10, 000) (Z=6.196, p<0.000). These major differences in training were also seen in postgraduate years even though overall headache teaching was greater in postgraduate than undergraduate training (p<0.000). Conclusions: Despite the high prevalence and morbidity of headache disorders, they receive less attention in training than conditions with similar prevalence. We propose that headache training opportunities should be improved in our region, particularly in the undergraduate course and preceptorships or fellowships in postgraduate years.